The Role of Invasive Hemodynamic Monitoring in Patients with Severe Mitral Regurgitation Undergoing Herniorrhaphy Operation - Kapitan, Titin Agustin; Adinda Putra Pradhana; Cynthia Dewi Sinardja (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Mitral regurgitation (MR) indeed presents challenges during noncardiac surgeries, especially as the severity of MR tends to increase with age and poses a higher risk of perioperative complications. Accurate hemodynamic monitoring becomes crucial in these cases to manage potential complications effectively. However, the standard monitoring in MR conditions during operation, such as TEE, is not always available, but there are other options for invasive monitoring, such as arterial lines, which provide accurate hemodynamic monitoring. Case presentation: A 64-year-old, male, presented with Reponible Lateral Inguinal Hernia with comorbid of severe mitral and tricuspid regurgitation alongside congestive heart failure. The patient was premedicated with fentanyl 25 mcg intravenously, followed by oxygen supplementation with 3 lpm nasal cannula and insertion of the arterial line. Anaesthesia was performed using a lumbar epidural technique, with the insertion of an epidural catheter in the L1-L2 intervertebral space, Reponible Lateral Inguinal Hernia. The local anesthesia agent chosen was plain bupivacaine with a concentration of 0.5% and a volume of 8 ml. The onset of action of epidural anesthesia is achieved within 20 minutes as long as the operation reaches a total blockade as high as T8. The patient is monitored with standard monitors and an artery line during surgery. There were no complaints of shortness of breath, chest heaviness, or chest pain felt by the patient during the operation. Conclusion: Epidural anesthesia technique can provide stable hemodynamics in patients with severe mitral-tricuspid regurgitation and congestive heart failure and hemodynamic monitoring plays an important role postoperatively to prevent further deterioration and maintain stability.